Universal CAR T cells targeted to HER2 with a biotin-trastuzumab soluble linker penetrate spheroids and large tumor xenografts that are inherently resistant to trastuzumab mediated ADCC - Nagy, Lőrinc; Mezősi-Csaplár, Marianna; Rebenku, István; Vereb, György; Szöőr, Árpád (Frontiers in Immunology, 2024)
CAR T cell therapies face challenges in combating solid tumors due to their single-target approach, which becomes ineffective if the targeted antigen is absent or lost. Universal CAR T cells (UniCAR Ts) provide a promising solution by utilizing molecular tags (linkers), such as biotin conjugated to monoclonal antibodies, enabling them to target a variety of tumor antigens. Recently, we showed that conventional CAR T cells could penetrate the extracellular matrix (ECM) of ADCC-resistant tumors, which forms a barrier to therapeutic antibodies. This finding led us to investigate whether UniCAR T cells, targeted by soluble antibody-derived linkers, could similarly tackle ADCC-resistant tumors where ECM restricts antibody penetration. We engineered UniCAR T cells by incorporating a biotin-binding monomeric streptavidin 2 (mSA2) domain for targeting HER2 via biotinylated trastuzumab (BT). The activation and cytotoxicity of UniCAR T cells in the presence or absence of BT were evaluated in conventional immunoassays. A 3D spheroid coculture was set up to test the capability of UniCAR Ts to access ECM-masked HER2+ cells. For in vivo analysis, we utilized a HER2+ xenograft model in which intravenously administered UniCAR T cells were supplemented with intraperitoneal BT treatments. In vitro, BT-guided UniCAR T cells showed effective activation and distinct anti-tumor response. Upon target recognition, IFNγ secretion correlated with BT concentration. In the presence of BT, UniCAR T cells effectively penetrated HER2+ spheroids and induced cell death in their core regions. In vivo, upon intravenous administration of UniCAR Ts, circulating BT linkers immediately engaged the mSA2 domain and directed effector cells to the HER2+ tumors. However, these co-treated mice died early, possibly due to the lung infiltration of UniCAR T cells that could recognize both native biotin and HER2. Our results suggest that UniCAR T cells guided with soluble linkers present a viable alternative to conventional CAR T cells, especially for patients resistant to antibody therapy and those with solid tumors exhibiting high antigenic variability. Critical to their success, however, is the choice of an appropriate binding domain for the CAR and the corresponding soluble linker, ensuring both efficacy and safety in therapeutic applications.